Short-Term Efficacy and Safety of Subcutaneous Tocilizumab in Rheumatoid Arthritis Patients in Pakistan: A Real-World Experience - Malik, Tashia; Saeed, Muhammad Ahmed; Ghani, Sumera; Butt, Nauman Ismat; Raja, Sumaira Farman; Ahmed, Nighat Mir (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the real-world efficacy and safety of subcutaneous Tocilizumab in patients with rheumatoid arthritis.Study Design: Case series.Place and Duration of Study: Department of Rheumatology, National Hospital and Medical Centre, Lahore Pakistan, from Aug 2019 to Dec 2020.Methodology: In this study, 33 patients receiving subcutaneous Tocilizumab 162 mg every two weeks as monotherapy or with conventional synthetic disease modifying anti-rheumatic drugs were followed per standard study protocol. Increasing or decreasing the dosing interval was allowed according to disease activity at the discretion of the treating rheumatologist. The primary outcome was patients achieving Low Disease Activity as per Clinical Disease Activity Index (>2.8-10.0) and Disease Activity Score-28(>2.6-3.2). The secondary outcome was a clinically meaningful improvement in Disease Activity Score -28 (reduction of ≥1.2 units in Disease Activity Score-28 score). Adverse events were recorded at each follow-up visit.Results: Of the 33 patients, 25(75.8%) were biologics-naive, 9(27.2%) patients achieved the target of Low Disease Activity as per Clinical Disease Activity Index (2.9-10.0) and 8(24.2%) patients achieved Low Disease Activity as per Disease Activity Score-28(2.7-3.2). At six months, the proportion of patients achieving clinically meaningful improvement (decrease ≥1.2) in Disease Activity Score -28 was 13(54.2%). Overall, 14(42.4%) patients developed adverse events and 3(9.1%) patients discontinued Tocilizumab owing to adverse events.Conclusion: Tocilizumab has been seen to be an effective biologic in only one-third of patients, and it was tolerated in twothirds of the patients.Keywords: Conventional synthetic disease modifying anti-rheumatic drugs, Efficacy, Rheumatoid arthritis, Safety, Subcutaneous tocilizumab.